Diagnostic use of abdominal ultrasound in detecting extrapulmonary tuberculosis or lymphoma in an HIV-endemic region - Ellouise C. Adams; Katherine Antel; Jenna L. Bailey; Karryn L. Brown; Dharshnee R. Chetty; David Richardson; Estelle Verburgh (Southern African Journal of HIV Medicine)
Background: Extrapulmonary tuberculosis (EPTB) is common among people living with HIV (PLWH). Abdominal ultrasound is an accessible investigation, frequently employed to support the diagnosis of EPTB, but may lead to misdiagnoses of diseases with overlapping clinical features, such as lymphoma.